Perceptual Congruence About Communication as Related to Satisfaction: Moderating Effects of Individual Characteristics - Hatfield, John D.; Huseman, Richard C. (Academy of Management Journal, 1982)
In a study of the relationship between perceptual congruence about communication and subordinate satisfaction, congruence about communication between supervisor and subordinate was found to be significantly related to satisfaction with work, supervision, and job satisfaction in general. Moderating effects of subordinates' individual characteristics on the congruence-satisfaction relationship were minimal.